The Mediation of Organizational Commitment among Perceived Organizational Support and Organizational Citizenship Behavior - Totiyah Husnah; Rini Sarianti (Human Resource Management Studies, 2024)
The present research intends to probe the degree to which perceived organizational support can have a profound effect on organizational citizenship behavior as being mediated via organizational commitment. at PT Telkom Akses Padang. It is a type of causal associative research using a quantitative and survey method. All data were gathered through questionnaires employing the total sampling technique, the total sample size represents 60 respondents. To test the hypothesis, we use SEM technique with the assistance of SmartPLS4 application. From the results, it was found that Perceived organizational support and organizational commitment display positive and significant impacts on organizational citizenship behavior. Besides, other outcomes also revealed that organizational commitment is capable of mediating the connection among perceived organizational support and organizational citizenship behavior